Cohort Study of Airway Mycobiome in Adult Cystic Fibrosis Patients: Differences in Community Structure between Fungi and Bacteria Reveal Predominance of Transient Fungal Elements - Kramer, Rolf (J Clin Microbiol, 2015)
The respiratory mycobiome is an important but understudied component of the human microbiota. Like bacteria, fungi can cause severe lung diseases, but their infection rates are much lower. This study compared the bacterial and fungal communities of sputum samples from a large cohort of 56 adult patients with cystic fibrosis (CF) during nonexacerbation periods and under continuous antibiotic treatment. Molecular fingerprinting based on single-strand conformation polymorphism (SSCP) analysis revealed fundamental differences between bacterial and fungal communities. Both groups of microorganisms were taxonomically classified by identification of gene sequences (16S rRNA and internal transcript spacer), and prevalences of single taxa were determined for the entire cohort. Major bacterial pathogens were frequently observed, whereas fungi of known pathogenicity in CF were detected only in low numbers. Fungal species richness increased without reaching a constant level (saturation), whereas bacterial richness showed saturation after 50 patients were analyzed. In contrast to bacteria, a large number of fungal species were observed together with high fluctuations over time and among patients. These findings demonstrated that the mycobiome was dominated by transient species, which strongly suggested that the main driving force was their presence in inhaled air rather than colonization. Considering the high exposure of human airways to fungal spores, we concluded that fungi have low colonization abilities in CF, and colonization by pathogenic fungal species may be considered a rare event. A comprehensive understanding of the conditions promoting fungal colonization may offer the opportunity to prevent colonization and substantially reduce or even eliminate fungus-related disease progression in CF.